A Study to Assess the Effectiveness of Pranic Healing Therapy on Backache among Adults At Pranic Healing Centre in Pune City - Ms Kaguiphullu Sylvia Gangmei1 , Sheela Upendra2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Pranic healing is a energy based therapy . It activates the healing meachanism in the bodyObjective : To assess the degree of pain among the adult on back pain.,to assess the effectiveness of Pranichealing therapy on backache among adults. And to determine the association between backpain and PranicHealing therapy with selected demographic variables variables Methods:. A quantitative approach andPre-experimental one-group pretest-posttest research design was used to assess the effectiveness of pranichealing therapy among adults group. study was conducted in a selected Pranic healing therapy centre inPune city more than 200 adult came for the therapy. Amongst them 40 samples were selected for the studywho fulfills the inclusion criteria.. Convenience sampling techniques was used for the selection of samplesin this study.Tool included three Sections . Part I – Demographic variable . Part II - modified Bayerchiro’spain scale to assess the symptoms of pain, stiffness, and physical function in patients with back pain. Thesamples were given a pretest , followed by Pranic healing therapy was given and post test is given. Result:Average pain score in pretest was 33.1 which decreased to 29.3 in posttest. T-value for this test was 9.3 with39 degrees of freedom. Corresponding p-value was small (less than 0.05), null hypothesis is rejected. This isevident that the Pranic healing therapy improved the backache among adults significantly Conclusion: Afterthe therapy given to the adult age group with backpain , pranic healing therapy is one of the most importantaspect to decrease pain without any side effects